What is the optimal rate of failed extubation? - Krinsley, James S (BioMed Central, 2012)
Failed extubation (FE), defined as reintubation 48 or 72 hours after planned extubation, occurs in a significant percentage of patients and is associated with a substantial burden of morbidity and mortality. This commentary reviews the literature describing FE rates and the clinical consequences of FE and proposes an 'optimal' rate of FE as well as avenues for future research.